2010
DOI: 10.1245/s10434-010-1250-6
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Time to Treatment and Survival Impact in Breast Cancer

Abstract: Interval from diagnosis to treatment of breast cancer within the same cancer center was longer at the CH than the UH. There was, however, no effect on overall survival. Time to treatment may not be a meaningful indicator of cancer care quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 28 publications
5
70
2
1
Order By: Relevance
“…In general, long waiting times are associated with poor access to services and poor quality of care. 2,3 However, delays can also be due to requests for a second opinion or time-consuming pathologist reviews that might affect treatment. 4 In addition, the high incidence of cervical cancer at early age has led to revised treatment strategies in young cancer patients, and many institutes consider different methods for preservation of fertility or ovarian function, including ovarian transposition and/or ovarian stimulation and oocyte retrieval prior to initiation of cancer treatment.…”
mentioning
confidence: 99%
“…In general, long waiting times are associated with poor access to services and poor quality of care. 2,3 However, delays can also be due to requests for a second opinion or time-consuming pathologist reviews that might affect treatment. 4 In addition, the high incidence of cervical cancer at early age has led to revised treatment strategies in young cancer patients, and many institutes consider different methods for preservation of fertility or ovarian function, including ovarian transposition and/or ovarian stimulation and oocyte retrieval prior to initiation of cancer treatment.…”
mentioning
confidence: 99%
“…In contrast, there are several studies that indicate otherwise, i.e., that delays in adjuvant treatment do not influence survival. 9,12,19,20 This controversy can be due to confounding factors, such as different patients selected and differas a continuous variable, the risk of death was increased 1.3-fold for each month of delay, independently of other well-established factors.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 This conflict cannot be easily resolved, because a prospective study to evaluate this variable and its possible confounding factors would be unethical. 12 Therefore, we conducted a retrospective cohort study to determine if an increased delay between surgery and the first adjuvant treatment is a risk factor for lower overall survival among women with invasive breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a delay of more than 6 months may affect outcome [38]. Others are showing that peri-operative delays had no impact on survival [39].…”
Section: Discussionmentioning
confidence: 99%